Comparative life cycle assessment of a mesh ultra-thin layer photobioreactor and a tubular glass photobioreactor for the production of bioactive algae extracts. (November 2021) - Sandmann, Michael; Smetana, Sergiy; Heinz, Volker; Rohn, Sascha
Highlights: The first study on Life Cycle Assessment (LCA) of microalgae antioxidant capacity. The study compared tubular (TBR) and mesh ultra-thin layer (MUTL) cultivation. LCA was performed for pilot industrial microalgae cultivation and processing. 1 kg dm of biomass produced with TBR had lower environmental impact. 1 mmol of antioxidative potential cultivated by MUTL had 5–10 times lower impact. Abstract: This study aimed at the comparison of two different photobioreactors with focus on technology and sustainability. The mesh ultra-thin layer photobioreactor (MUTL-PBR) exhibited around 3-fold biomass based space–time-yield and an around 10-fold specific antioxidant capacity than the traditional reference photobioreactor. Life cycle assessment (LCA) was done under autotrophic conditions in both pilot scale reactors with focus on biomass production and on antioxidant capacity of the biomass, respectively. Biomass production within the reference reactor showed a lower environmental impact in most categories. A significantly higher energy demand for mixing and cooling of the cell suspension within the MUTL-PBR is the major reason for its environmental burden. This relates to high impacts in the categories "non-renewable energy" and "global warming potential" per kg biomass. Comparing algal antioxidant capacity, environmental impact of the MUTL cultivation was 5–10 times lower. This clearly illustrates the potential of MUTL-PBR for sustainable production of bioactive substances.